Development of Interactive Power Point Based Learning Media on Principles of Land Measurement for Construction - Carolus Carles Rejeki Gulo; Envilwan Berkat Harefa; Arisman Telaumbanua; Adrianus Zega (Edumaspul: Jurnal Pendidikan, 2024)
The problem found by researchers through observations of the learning process at SMKNegeri 1 Mandrehe Barat, namely that the learning process using media is still not optimal.The aim is to develop power -based learning media for class X DPIB I n t e r a c t i v ePoint on the material Principles of Land Measurement for Construction Work to determinethe Feasibility, Practicality and Effectiveness of Media Products.This type of research usesthe ADDIE ( Analize, Design, Development, Implementation, Evaluation ) model. Theinstruments used in this research were validation questionnaires for feasibility tests, studentresponse questionnaires for practicality tests, and essay tests to test the effectiveness oflearning outcomes. Power Point -based media on material on Principles of LandMeasurement for Construction Work. Very Eligible Criteria based on 90% material expertassessment. Based on 98% language expert assessment. Based on a Design expertassessment of 92%. Media Practicality is categorized as very practical based on 90%individual trials and 91% field trials. The criteria are very effective with an effective mediapercentage of 94%. So it can be concluded that the Power Point- based learning mediadeveloped is very feasible, practical and effective for use in the learning process.suggestions from researchers (1) for students it is hoped that with Power Point- based mediato increase effectiveness and critical thinking in the material Principles of LandMeasurement for Construction Work, (2) for teaching staff it can add innovation in usingmedia (3) for researchers , can use this research as subsequent research to determine thefeasibility of the product.